Insight into the genome data of commercially important giant kelp Macrocystis pyrifera - Paul, Sujay; Salavarría, Erika; García, Katherine; Reyes-Calderón, Alonso; Gil-Kodaka, Patricia; Samolski, Ilanit; Srivastava, Aashish; Bandyopadhyay, Anindya; Villena, Gretty K. (Elsevier, 2022)
Kelps or brown algae are a wide group of marine macroalgae that play an important role in aquatic ecosystems and generally have high commercial value. To facilitate brown algal studies, we report the complete genome sequence of the largest kelp Macrocystis pyrifera. The whole genome is ∼428 Mb in size, comprises 44,307 scaffolds with an average GC content of 47%, and is predicted to contain a total of 24,778 genes. 18S sequence-based phylogenetic analysis revealed that littoral brown seaweed Scytosiphon lomentaria is the closest species of M. pyrifera. Numerous genes identified in this dataset are involved in genetic information processing, signaling, and cellular processes, carbohydrate metabolism, and terpenoids biosynthesis.